2022
DOI: 10.1155/2022/6065516
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Inhibits Gastric Cancer Growth and Hepatic Metastasis by Reducing Syntenin Expression and STAT3 Phosphorylation

Abstract: Gastric cancer (GC) is a common malignant tumor worldwide and poses a serious threat to human health. As a traditional Chinese medicine, Huaier (Trametes robiniophila Murr.) has been used in the clinical treatment of GC. However, the mechanism underlying the anticancer effect of Huaier remains poorly understood. In this study, we used in vivo imaging technology to determine the anticancer effect of the Huaier n-butanol extract (HBE) on orthotopic and hepatic metastasis of GC mouse models. We found that HBE sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Huaier granule has potential advantages in antitumor therapies involving multiple targets and pathways. n-Butanol extract of Huaier can inhibit the syntenin/ STAT3 signaling pathway to inhibit tumor growth and metastasis (Shi et al, 2022). Huaier has been verified to have anti-cancer effects by inhibiting cancer cell growth and energy metabolism through the PI3K/AKT/HIF-1α pathway (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Huaier granule has potential advantages in antitumor therapies involving multiple targets and pathways. n-Butanol extract of Huaier can inhibit the syntenin/ STAT3 signaling pathway to inhibit tumor growth and metastasis (Shi et al, 2022). Huaier has been verified to have anti-cancer effects by inhibiting cancer cell growth and energy metabolism through the PI3K/AKT/HIF-1α pathway (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…All cell lines were recently authenticated by short tandem repeat authentication and tested for mycoplasma contamination. NUGC-4, MKN-74, AZ-521, MKN-1, NUGC-3, HGC-27, MKN-45, and GES-1 cells were cultured in RPMI-1640 (BasalMedia, Shanghai, China), and AGS cells were cultured in Ham’s F12 (Cienry, Hu Zhou, China) containing 10% fetal bovine serum (FBS, Gibco, Grand Island, USA) and 1% penicillin/streptomycin (Kino Co., Ltd., Hangzhou, China) at 37 °C under 5% CO 2 in a cell culture incubator [ 35 ]. NAC, a ROS scavenger, was purchased from Sigma–Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In order to retain more bioactive components with poor solubility or heat sensitivity, an alternative method uses alcoholic solvents to obtain the Huaier n-butanol extract (HBE, NEH or TRMBE), which includes flavonoids as the major component with a proportion of 51.4% in the final product. In vitro and in vivo experiments demonstrated beneficial health effects of HBE in combating tumor growth, metastasis and modulating immune function while in vivo toxicity remains negligible even in high dose (17,(20)(21)(22)28).…”
Section: Butanol Extract Of Huaiermentioning
confidence: 99%
“…Animal experiments provide strong evidence to the safety of Huaier. Various aspects of Huaier-treated animals that could indicate possible toxicity, such as body weight ( 22 , 31 , 34 , 90 , 119 122 ), behavior ( 21 , 30 , 123 ), appetite and food intake ( 112 , 124 ), histology of major organs (heart, liver, kidney, lungs, spleen, pancreas and brain) ( 17 , 20 , 32 , 33 , 125 ), blood assay ( 20 , 23 ), liver and kidney function ( 29 ), and animal survival ( 112 ), have been thoroughly examined in numerous studies. However, almost all of these studies reported negligible signs of toxicity in animals, indicating the safety of Huaier in preclinical studies.…”
Section: Toxicitymentioning
confidence: 99%